ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CONTINUANCE INTENTION: Studi Kasus pada Pengguna Go-Food di Kota Bandung - Banjarnahor, Yolanda May Emmanuella; Setyorini, Retno (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
This research was conducted to determine and analyze the factors that influence Continuance Intention of Go-Food users in Bandung. The purpose of this study was to determine how much influence Habit on Continuance Intention of Go-Food users in Bandung, to find out how much influence Perceived Usefulness has on Continuance Intention of Go-Food users in Bandung, to know how much influence Perceived Enjoyment has on Continuance Intention of Go-Food users in Bandung, knowing how much influence Perceived Ease of Use has on the Continuance Intention of Go-Food users in Bandung. The independent variables are Habit, Perceived Usefulness, Perceived Enjoyment and Perceived Ease of Use. While the dependent variable is Continuance Intention. This research uses quantitative methods with descriptive research type. The population in this study were Go-Food users in Bandung. The sample technique used nonprobability sampling method with purposive sampling, that is as many as 100 respondents. The data analysis technique used multiple linear regression analysis. The conclusion of this study is that Habit, Perceived Usefulness, Perceived Enjoyment have a positive and significant effect on Continuance Intention. Meanwhile, Perceived Ease of Use has no positive and significant effect on Continuance Intention